Exploring higher education policy reforms in different contexts: A comparative study of Australia, Canada and Egypt. - Abdel-Tawab, Eman Mahmoud (AUC Knowledge Fountain, 2019)
This study is concerned with exploring higher education policy and reforms enacted by three diverse countries, Australia, Canada, and Egypt, to improve the quality of education and its relevancy to job market needs. The purpose of this study is to develop a better understanding of similarities and differences in context and motivations for reform and the subsequent results across the three countries and thus identify the lessons learned. This, in turn, will provide an answer to the prominent question of how can Egypt benefit from the higher education reform journeys undertaken by Australia and Canada. The study employs a “simultaneous comparative analysis,” following Bereday’s four–step method: description, interpretation, juxtaposition, and simultaneous comparison. It takes into account the socio-economic context, historical background, and cultural context of each of the three countries. Next, it explores the main higher education reform initiatives, challenges and results in each country. The main findings explored in this study reveal the urgent need for quality audit procedure to assess each institution’s effectiveness in achieving its goals. It also advocates for assuring and improving the quality of higher education through building self-regulating system. The findings also learn from the Australian experience in providing vocational and technical education, which focused on providing skills for the job market. The study concludes that a quality assurance system is more powerful than accreditation system, as it focuses on student learning outcomes. There is much to learn from policy and practice in Australia to maintain and assure quality. The study recommends conducting consultation with representatives of all stakeholders prior to the development of a new program in reference to the Canadian experiences. Moreover, the role of policy and decision makers must strengthen quality assurance system in the institution internally and from an authoritative agency externally. The study recommends that Egypt prioritizes the completion of accreditation of its all higher education institutions and revisit its admission policy to HE.